Zaščita otrok žrtev kaznivih dejanj v (pred)kazenskem postopku - Janjatović, Dajana (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2020)
The issue of secondary victimisation of children victims of criminal offences because of their participation in the (pre)criminal procedure has long been the subject of discussions within the victimological community. Protective measures, and legislation reforms related thereto, play a key role in creating a child-friendly justice system, however, they are often too slow, inconsistent, or insufficiently implemented in practice. This discussion deals with the development, good practices, and shortcomings of Slovenian legislative solutions in the field of protection of children victims of criminal offences in (pre) criminal procedures.
Keywords: kazensko pravo; kazniva dejanja